2017
DOI: 10.1111/are.13564
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary bamboo charcoal supplementation on growth and serum biochemical parameters of juvenile common carp (Cyprinus carpioL.)

Abstract: This study investigated the effect of dietary bamboo charcoal (BC) supplementation on the growth performance and health status of juvenile common carp (Cyprinus carpio L.). A 63-day feeding trial was carried out wherein the carp were reared on diets containing increasing levels of BC (0%, 0.5%, 1%, 2% and 4%). Treatment with BC did not produce any obvious effect (p > .05) on the growth performance of the juvenile common carp and on the overall muscle fatty acid composition. However, significant improvements (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…In China, a dietary bamboo biochar was added to the feed of juvenile common carps at rates from 1% to 4% (Mabe et al, 2018). The biochar treatments did not produce any obvious effect on the growth performance of the carps compared to 0% control.…”
Section: Resultsmentioning
confidence: 99%
“…In China, a dietary bamboo biochar was added to the feed of juvenile common carps at rates from 1% to 4% (Mabe et al, 2018). The biochar treatments did not produce any obvious effect on the growth performance of the carps compared to 0% control.…”
Section: Resultsmentioning
confidence: 99%
“…ALT, AST, and ALP plasma levels decreased drastically at bamboo charcoal levels of 0.5% and 1% in red tilapia after a 60 day feeding trial [ 34 ]. In carp ( Cyprinus carpio L.), it was reported that the plasma levels of ALT, AST, and ALP were significantly lower when the bamboo charcoal content in the feed was 1–4% [ 25 ]. Nevertheless, the optimal level of dietary bamboo charcoal or activated carbon may vary between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effects of dietary charcoal supplementation in animals have largely focused on mammals and some fish species, with a particular focus on animal growth [22][23][24][25]. However, to the best of our knowledge, the effects of dietary charcoal supplementation on trace element uptake and antioxidant performance in fish have not been previously characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The hepatopancreas is the important digestive organ in fish (Liu et al, ). Significant rises in the activities of GOT and GPT in plasma are the important indications of hepatopancreas damage including degeneration, damage (rupture and leakage), and/or necrosis of hepatocytes in fish (Akrami, Gharaei, Mansour, & Galeshi, ; Mabe et al, ), which may result from the toxicity of certain xenobiotics. Data here showed that trichlorfon caused the increase in the activities of GOT and GPT in plasma of carp.…”
Section: Discussionmentioning
confidence: 99%